(3cJGH aj GdMOhOs
(3ChdgG (B:s
(3dCfg jefY ef eYGhOI GdaYd GdPi MO Ydjg hGdgfOSi eKd MO GdOjGQ hGdBKGQ GdPi jefY ef ENJdGWgG HeG ShGgG s
(3BNQgG (B:s
(3agPG eG MVQfi Ydi GdENJUGQ, hbO HSWJ GdcdGe ai CcKQ gPg GdMOhO ai JbQjH GdCUhd hJQJjH GdaUhd hChVMJ GdCeKdg hGdMLGL ai eSGdc GdLOd ai cJGH EMcGe GdeMGVQI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3ai JYQjagGs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs